Galaxy And Mass Assembly (GAMA): extended intragroup light in a group at z = 0.2 from deep Hyper Suprime-Cam images. Issue 1 (24th November 2022) - Martínez-Lombilla, Cristina; Brough, Sarah; Montes, Mireia; Baena-Gallé, Roberto; Akhlaghi, Mohammad; Infante-Sainz, Raúl; Driver, Simon P; Holwerda, Benne W; Pimbblet, Kevin A; Robotham, Aaron S G
ABSTRACT: We present a pilot study to assess the potential of Hyper Suprime-Cam Public Data Release 2 (HSC-PDR2) images for the analysis of extended faint structures within groups of galaxies. We examine the intragroup light (IGL) of the group 400138 ( M dyn = 1.3 ± 0.5 × 10 13 M⊙, z ∼ 0.2) from the Galaxy And Mass Assembly (GAMA) survey using Hyper Suprime-Cam Subaru Strategic Program Public Data Release 2 (HSC-SSP PDR2) images in g, r, and i bands. We present the most extended IGL measurement to date, reaching down to $μ _{g}^{\rm {lim}}=30.76$ mag arcsec −2 (3σ; 10 × 10 arcsec 2 ) at a semimajor axis of 275 kpc. The IGL shows mean colour values of g − i = 0.92, g − r = 0.60, and r − i = 0.32 (±0.01). The IGL stellar populations are younger (2–2.5 Gyr) and less metal rich ([Fe/H] ∼ −0.4) than those of the host group galaxies. We find a range of IGL fractions as a function of total group luminosity of ${\sim} 2\!-\!36 {{\ \rm per\ cent}}$ depending on the definition of IGL, with larger fractions the bluer the observation wavelength. The early-type to late-type galaxy ratio suggests that 400138 is a more evolved group, dominated by early-type galaxies, and the IGL fraction agrees with that of other similarly evolved groups. These results are consistent with tidal stripping of the outer parts of Milky Way-like galaxies as the main driver of the IGL build-up. This is supported by the detection of substructure in the IGL towards the galaxy member 1660615 suggesting a recent interaction (<1 Gyr ago) of that galaxy with the core of the group.